EFFECTS OF ADDING IRAQI PROBIOTIC ON SOME HEMATO - BIOCHEMICAL PARAMETERS IN BROILER CHICKENS - A. F. Abdul-majeed (Mesopotamia Journal of Agriculture)
This study was carried out to know the effects of adding the probiotic on some hemato-biochemical parameters in broiler chickens . 200 of broiler chickens (Cobb) one day-old were randomly divided into 4 groups(50 chicks / each / 2 replicates ) which used as follows:T1 control fed standard ration ,while other treatments groups by adding of probiotic to the ration (2,4 and 6 Kg probiotic/Ton of ration ) on respectively .Chicks raised on standard conditions to the age of marketing (42 days ) .Blood samples were obtained two times at day (21 and 42 ) for studying physiological changes. Results revealed a significant increase in blood glucose levels in the probiotic treated groups in the 2nd period as compared with the 1st period at p≤0.05. Also there is a significant decrease in the cholesterol levels in both period as compared with control, the decrease was proportionally- related with probiotic concentrations at p≤0.05. Results also showed a significant increase in total serum protein, albumen and globulin concentrations in the 4th group in the 1st period as compared with control, and in the 2nd ,3rd and 4th groups in the 2nd period as compared with the 1st period. Also there is a significant increase in RBCs count, Hb and MCHC as compared with control. In conclusion, results revealed that the probiotics treatment improve some important hematological and biochemical parameters that enhances the bird immunological and reproductive performance.